The DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN TANZANIA: AN AUTOREGRESSIVE DISTRIBUTED LAG APPROACH - Mwigeka, Samwel (PT Inovasi Pratama Internasional, 2023)
Foreign Direct Investment (FDI), as a source of external capital to enhance growth, has become extremely important in light of the decreases in official lending, brings its infusion of a corporate culture that changes the way business is done, brings managerial know-how and best practices, provide access to international markets, transfer technology and innovation, introduce competitive pressures in previously closed markets and becoming the principal driver for the growth of local business. Given those critical issues, it is very crucial to understand the determinants of FDI, which can be used by the country to regulate and be assured of sustainable growth and development. With this regard this study investigated the determinants of FDI in Tanzania, using secondary time series data from 1990 to 2020. In attempting this, the study utilized the Autoregressive Distributed Lag (ARDL) in combination with the Error Correction Model (ECM) and bounds testing procedure. The results indicate that in the long run, the coefficients of gross capital formation, exchange rate, and financial structure are statistically insignificant with the required direction of relationship with the exception of real GDP, trade openness, and inflation rate while in the short-run the results have shown the opposite of the results in the long-run. The results above indicate a great need for a country to emphasize domestic investment as this has shown a positive impact in attracting foreign direct investment in the short-run, with higher real GDP implying a large market thus suitable for market-seeking investments and also does promote export. The country needs to strengthen its monetary policy to ensure a stable exchange rate and price as it has shown a converse relationship with foreign direction investment thus attracting more market-seeking investments.